Kelussia odoratissima Mozaff. as a rich source of essential fatty acids and phthalides - Ghasemi Mehdi; Mirlohi Aghafakhr; Ayyari Mahdi; Shojaeiyan Abdolali (Shahrekord University of Medical Sciences, 2015)
Introduction: The present study is the first assessment of the fatty acids of leaf and essential oil compositions of new three habitats of aerial parts of K. odoratissima. Methods: The aerial parts of K. odoratissima from the three habitats were dried. The essential oils were obtained by hydrodistillation for 3 h in a Clevenger-type apparatus, then the analysis of the components was carried out using gas chromatography-mass spectrometry. To study the oil yield and fatty acids, the dried leaves subjected to extraction in hexane by using Soxhlet Apparatus. To analyze fatty acids from the oil fractions by gas chromatography technique, the oil was subjected to transesterification to obtain the fatty acid methyl esters, which, were dissolved in hexane and subjected to GC analysis. Results: According to the results, a total of 43 components, the major constitutes of essential oil compositions were (Z)-Ligustilide (76.45%), Unknown-A (4.47%), (E)-Ligustilide (2.57%), (Z)-Butylidene phthalide (2.37%), 5-pentyl cyclohexa-1,3-diene (1.57%) and Kessane (0.77%) in K. odoratissima. The sixteen fatty acids were separated from the oil (5% yield per 100 g dry matter). Linoleic acid (25.46%), α-Linolenic acid (16.66%), Palmitic acid (11.92%), Oleic acid (9.33%), Stearic acid (4.72%), Petroselinic acid (2.53%), Arachidonic acid (2.51%) and Erucic acid (1.76%) were major fatty acids. Conclusion: Generally, K. odoratissima is a rich source of essential fatty acids and phthalide derivatives, specially (Z)-ligustilide. This study was presented valuable information about the phytochemical properties, which can be useful for the future researches on the pharmacological effects of K. odoratissima.